PENGEMBANGAN WISATA RELIGI SYEKH NAWAWI AL-BANTANI SEBAGAI UPAYA MENSEJAHTERAKAN EKONOMI MASYARAKAT DI KECAMATAN TANARA KABUPATEN SERANG - Ubay Haki (LP2M Universitas Bina Bangsa, 2022)
Banten Province is already famous for its history, especially Islamic historical relics, artifacts, sites, mosques, petilasan and tombs, are forms of historical heritage that can be developed into one of the national tourist destinations. One type of tourism that is now developing is religious tourism. Serang Regency is known as the Santri area, in this case the Tanara Subdistrict, which is part of the Serang Regency area. There are relics of the great cleric of the archipelago, Sheikh Nawawi Al-Bantani, artifacts, petilasan and tombs of scholars and old mosques that have historical value. The tombs of the clerics and historic mosques were visited by pilgrims who not only came from the Banten area but also came from various regions from the islands of Java and Sumatra. In an effort to develop the potential of existing religious tourism, it is deemed necessary to conduct a study related to the development of religious tourism in Tanara District. The aims of this study are: (1) to analyze the distribution of religious-based tourism objects that can be developed as religious tourism objects; (2) Analyzing the problems and constraints faced related to the development of existing religious tourism based on; (3) Establish recommendations/policy strategies that need to be taken in the development of religious tourism in Tanara District. This research is a descriptive qualitative type with data collection techniques through in-depth interviews with informants who have been selected based on their competence to knowledge of religious locations in Tanara. The results showed that there were 15 religious tours in Tanara District. The obstacles faced are related to facilities and infrastructure, the weak carrying capacity of local resources for the existence of tourist objects, and the lack of tourism marketing with religious themes. To overcome these obstacles, the strategies that can be carried out are the development of tourism facilities and infrastructure, the development of local resources, and the development of marketing